Festive season balancing groceries optimization / Fairuz Mohamed Razi - Mohamed Razi, Fairuz (2012)
This research uses Genetic Algorithms concept and technique to solve an optimization problem in shortage in supply-demand during festive season which is during Hari Raya Aidilfitri. An Artificial Intelligence method or technique is selected to provide a solution to this problem. The cause of the shortage in supply-demand is taken to be implemented in the Genetic Algorithms optimization concepts. The objective of this research is gained from the understanding of the problem statement. The main idea of this research is to create a system prototype that uses Genetic Algorithms process engine that can calculate an optimization of the customer demand. The methodology of this project is divided into several phases. The phases are information gathering, system requirement, data collection, system design and implementation, result analysis. The most important part is during system design and implementation. In this phase, method use in Genetic Algorithm to optimize the system prototype is Rastrigin's function to calculate the fitness of the chromosomes.